2018
DOI: 10.1590/1982-0216201820111917
|View full text |Cite
|
Sign up to set email alerts
|

Desembaralhando: a mobile application for intervention in the problem of dyslexic children mirror writing

Abstract: Purpose: to present a new application for mobile devices, referred to as Desembaralhando, for intervention in the problem of dyslexic children mirror writring. Methods: the development of the application is the result of a set of clinical and speech therapy information and experiences, which points out frequency of letter mirroring as a challenging problem in children with dyslexia. The application, developed in the light of the multisensory approach, was created by a multidisciplinary team of computer scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
(22 reference statements)
0
4
1
10
Order By: Relevance
“…For the hand method, the left hand represents b and the right hand represents d and this method is more effective compared to the mirror method. However, these findings do not support the previous research [31]. It demonstrated that rotating the letters in their own axes (mirror method) in the Desembaralhando mobile application was facilitated the learners to recognize the visual difference of the letters such as d and b, q and p, a and e.…”
contrasting
confidence: 79%
“…For the hand method, the left hand represents b and the right hand represents d and this method is more effective compared to the mirror method. However, these findings do not support the previous research [31]. It demonstrated that rotating the letters in their own axes (mirror method) in the Desembaralhando mobile application was facilitated the learners to recognize the visual difference of the letters such as d and b, q and p, a and e.…”
contrasting
confidence: 79%
“…En esta línea, se han realizado investigaciones que utilizan herramientas tecnológicas para facilitar la intervención en los trastornos específicos del aprendizaje de la lectura y escritura. Por ejemplo, Cidrim et al, (2018) desarrollan una aplicación multisensorial para teléfonos móviles, que permiten a los niños y niñas con dislexia afrontar la escritura en espejo.…”
Section: Aportaciones a La Dislexia Desde El áMbito De La Tecnologíaunclassified
“…This application is designed to encourage literacy in dyslexic children involving topics such as recognizing letters, memorizing letters, remembering letters, writing letters, and sounding letters correctly (Yedra & Aguilar, 2022). Educators, dyslexic children, and parents can also use this application to stimulate learning activities at home (Cidrim et al, 2018).…”
Section: A Introductionmentioning
confidence: 99%